The Influence of Financial Literacy, Overconfidence Bias, and Herding Behavior on Stock Investment Interest among Generation Z Students - Tia, Fenika Elis; Bella, Cinthya; Muhammad, Mahathir (JURNAL MANAJEMEN MOTIVASI, 2026)
This study investigates the influence of financial literacy, overconfidence bias, and herding behavior on stock investment interest among Generation Z students aged 17–27. Employing a quantitative approach, data were collected via questionnaires from 180 respondents and analyzed using statistical methods. Results reveal that financial literacy significantly and positively affects investment interest. In contrast, overconfidence bias and herding behavior show no significant individual effects. Nevertheless, collectively, all three variables significantly influence stock investment interest. These findings underscore the critical role of financial education and psychological awareness in fostering rational investment behavior among young investors.